Distribution of High-Fluoride Groundwater in Dong Xuan District (Phu Yen Province), Vietnam, and Assessment of the Human Health Risk - Rowsell, Andrew E. (Curtin University, 2014)
Electrical resistivity imaging (ERI) and groundwater solute transport modelling are developed for recovery of the hydrogeological architecture of coastal margins. ERI acquisition and processing parameters, along with the influence of hydraulic anisotropy and heterogeneity in karstic aquifers, are explored with examples selected along more than 100 km of coastline proximal to Perth Western Australia. The methods will contribute to accurate predictive groundwater modelling and sustainable management of high-quality coastal aquifers worldwide.